Development of quality indicators for diabetes care in community pharmacies: a modified Delphi method - Kayo Ueda; Hiroshi Okada; Shota Suzuki (BMC Public Health, 2026)
Abstract Background Type 2 diabetes is a common chronic condition requiring continuous management. Without a healthy lifestyle and regular treatment, it can lead to severe complications that greatly reduce the patients’ quality of life. Although support for medication management is well-studied and recommended in clinical guidelines, there is a growing need for support that empowers patients by considering their values and lifestyles. Such approaches enhance motivation for treatment and encourages long-term adherence. Recently, the role of community pharmacists in type 2 diabetes care has gained attention because of their significant impact in improving patient outcomes. This study aimed to develop quality indicators (QIs) to assess type 2 diabetes care provided by community pharmacists. Methods We used a modified Delphi method informed by the RAND/UCLA Appropriateness Method. Candidate indicators were generated through a systematic review of clinical practice guidelines and existing QIs, and then evaluated by a multidisciplinary panel that included a patient with type 2 diabetes. Consensus was achieved through two rounds of online rating using structured questionnaires, with anonymised aggregated results and comments shared by email between rounds. Predefined adoption criteria were used to determine which indicators were included in the final set. Results The multidisciplinary panel consisted of 12 members: two diabetes specialists, four community pharmacists, two nurses or public health nurses, one registered dietitian, two exercise specialists, and one patient. Through a systematic review, we identified 134 recommendations from three clinical practice guidelines and one existing QI, from which 29 candidate indicators that could be measured by community pharmacists were developed. After two rounds of panel evaluation, all 29 indicators achieved consensus and were adopted. Conclusions Using a modified Delphi method, we developed 29 QIs for evaluating lifestyle support provided by community pharmacists to patients with type 2 diabetes. These indicators may help community pharmacists monitor and improve the quality of lifestyle support provided to patients with type 2 diabetes.